Downstaging Therapies for Unresectable Hepatocellular Carcinoma Prior to Hepatic Resection: A Systematic Review and Meta-Analysis - Chen, Xinyu; Lai, Lin; Ye, Jiazhou; Li, Lequn (Frontiers in Oncology, 2021)
Introduction: Hepatocellular carcinoma (HCC) is a high-grade malignant disease with unfavorable prognosis, and although surgical therapy is necessary, not all patients with HCC are suitable candidates for surgery. Downstaging as preoperative therapeutic strategy, which can convert unresectable HCC into resectable HCC, intends to increase the resection rate and improve prognosis. Methods: We searched multiple databases updated to December 30, 2020, for studies on transcatheter arterial chemoembolization (TACE), Yttrium 90 microsphere selective internal radiation (SIR)/transcatheter radioembolization (TARE), hepatic arterial infusion (HAI) and systemic treatment as downstaging treatment before resection for patients with unresectable HCC. Results: A total of 20 comparative and non-comparative studies were finally included in the meta-analysis. The pooled downstaging rate of hepatic resection (HR) was 14% [95% confidence interval (CI) 0.10-0.17) with significant heterogeneity (I2= 94.51%). The chemotherapy, combination, and non-cirrhosis groups exhibit higher rates of downstaging, but these differences were not significant. For comparative studies, the overall survival (OS) rates of resection after downstaging were far better than those inpatients who receivedlocoregional therapy (LRT) or systemic treatment alone at1-year (RR 1.87, 95%CI 1.48-2.38), 3-year (RR 5.56, 95CI 2.55-12.10) and 5-year (RR 5.47, 95%CI 2.22-13.49). In addition, the pooled disease-free survival (DFS) rates in patients undergoing HR after successful downstaging were 78% (95%CI 0.62-0.93) at 1-year, 47% (95%CI 0.25-0.68) at 3-year and 46% (95%CI 0.32-0.59) at 5-year. And the pooled OS rates were 88% (95%CI 0.82-0.95) at1-year, 64% (95%CI 0.59-0.69) at 3-year and 42% (95%CI 0.29-0.54) at 5-year. Conclusions: Downstaging may serve as a screening tool to identify patients who might benefit from surgery. Resection after successful downstaging can improve prognosis.